The Host Protein Aquaporin-9 is Required for Efficient Plasmodium falciparum Sporozoite Entry into Human Hepatocytes - Amanzougaghene, Nadia; Tajeri, Shahin; Yalaoui, Samir; Lorthiois, Audrey; Soulard, Valérie; Gego, Audrey; Rametti, Armelle; Risco-Castillo, Véronica; Moreno, Alicia; Tefit, Maurel; van Gemert, Geert-Jan; Sauerwein, Robert W.; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Hepatocyte invasion by Plasmodium sporozoites represents a promising target for innovative antimalarial therapy, but the molecular events mediating this process are still largely uncharacterized. We previously showed that Plasmodium falciparum sporozoite entry into hepatocytes strictly requires CD81. However, CD81-overexpressing human hepatoma cells remain refractory to P. falciparum infection, suggesting the existence of additional host factors necessary for sporozoite entry. Here, through differential transcriptomic analysis of human hepatocytes and hepatoma HepG2-CD81 cells, the transmembrane protein Aquaporin-9 (AQP9) was found to be among the most downregulated genes in hepatoma cells. RNA silencing showed that sporozoite invasion of hepatocytes requires AQP9 expression. AQP9 overexpression in hepatocytes increased their permissiveness to P. falciparum. Moreover, chemical disruption with the AQP9 inhibitor phloretin markedly inhibited hepatocyte infection. Our findings identify AQP9 as a novel host factor required for P. falciparum sporozoite hepatocyte-entry and indicate that AQP9 could be a potential therapeutic target.